CERVICAL LENGTH ASSESSMENT DURING PREGNANCY USING ULTRASOUND MEASURES IN DUHOK CITY - AHMAD, DILGASH HAMEED; ALI, SOHAIB HASAN; SAEED, MAYSALOON SHAMAN (Journal of Duhok University, 2021)
Preterm birth has been regarded as a major cause of perinatal morbidity and mortality with an incidence ranging from 5-18 % worldwide. Early screening of pregnant women at risk of preterm delivery and managing it correctly are essential aids to reduce the predictable complications associated with prematurity Objective: The main aim of the study was to assess the true and acuurate cervical measuremants that predict the clear definition and cut values of the cervical incompetence in second trimester pregnant women by using transabdominal and transvaginal Ultrasound . More specofc aim of the study was looking for the accuracy of transabdominal ultrasound in measuring the cervical length for prediction of preterm birth when compared with transvaginal ultrasound, assessment of the mean cervical lengthin the second trimester pregnancy , the correlation between both of these modalities in each case , finding the clear cut off value of transabdominal Ultrasound measurement to be further assessed by transvaginal Ultrasound . Materials: A cross sectional prospective study done on ninety-three pregnant women between 12-22 weeks of gestation who were referred between March to November of 2018in thisprospective study ,their cervical lengths were assessed by using transabdominal Ultrasound , using Transvaginal Ultrasound as the reference, both methods were correlated forvariance. Results: The mean transabdominal cervical length measurements was seen to range (34.3 ± 5.8 mm) while the mean transabdominal cervical length measurements was seen to range (35.9 ± 4.4 mm). The mean transabdominal cervical length was shorter than the mean transvaginal cervical length by an average of 1.6 mm. The 10th percentile of transabdominal and transvaginal cervical length was 27 mm and29.4 mm, respectively. The two groups that showed significant difference between the two scanning methods were the 25th-50th centile group (TACL) of 33-37 mm) with p = 0.019, and the 50th-75th centile group (TACL) of 37-40 mm) with p =0.001 , the clear cut value of 27 mm was the value considered to revert fron TAUS to TVUS for CL assessment Conclusion:TAUS was found to be an initial CL screening method in the second trimester pregnant women generally while from 12- 14 weeks GA specifically the TVUS is preferred for this measurement ,a cut-off value of 27 mm is used to revert to TVUS for CL assessment instead of TAUS.